Pengalaman Awal Tindakan MitraClip di Pusat Jantung Nasional Harapan Kita, Jakarta - Prima Almazini; Nani Hersunarti; Rarsari Soerarso; Bambang Budi Siswanto; Doni Firman; Amiliana M Soesanto (The Indonesian Heart Association, 2015)
Background: Percutaneous mitral valve repair (PMVR) with MitraClip is considered as an optional treatment for patients with significant MR who are high risk for having surgery. This novel therapy is less invasive, safe, and effective for MR reduction, and hence improve symptoms of heart failure, as well as reverse left ventricle remodeling. The purpose of this study was to report the early experience of Mitraclip procedure for treating significant MR at the National Cardiovascular Center Harapan Kita.Methods: This retrospective study was conducted at National Cardiovascular Center Harapan Kita Hospital, Jakarta. The data was retrieved from computerized database and medical records from February 2014 to January 2015, and then analyzed with SPSS.Results: A total of 6 patients with age 51 - 75 years old, underwent MitraClip procedure. Of all patients, the MR were severe in 5 patients and moderate in 1 patient. One was female and 5 were male. Among these patients, 2 were degenerative MR and 6 were functional MR. Two patients were treated with single MitraClip and 4 patients required double MitraClip. Post proccedure, there was reduction of MR to mild was achieved in 2 patients and to moderate in 4 patients. The left ventricular end diastolic dimension decreased from 66 ± 6.5 mm at baseline to 59 ± 7.3 mm (p=0.04) and end systolic dimensions decreased from 50 ± 10.6 mm at baseline to 48 ± 10.0 mm before discharge (p=0.27) as evaluated from predischarge echocardiography. At one month after procedure, 2 patients were in New York Heart Association (NYHA) functional class I and 4 patients were in class II. In-hospital mortality was 0%. Only 1 patient was re-hospitalized after procedure due to heart failure.Conclusion: From our early experience, MitraClip was considered an effective and safe option for patients with functional and degenerative MR who are at high risk for open-heart surgery. Left ventricle dimension, NYHA functional class, MR reduction, and re-hospitalization rate were improved after procedure.